Community Service: Training on Produced Dishwashing Soap from Waste Cooking Oil for Strengthening Gampong Blang Ara Community Income - Jalaluddin, Jalaluddin; Suryani, Ade Irma; Suryani, Irma; Megawati, Megawati; Sakir, A; Halimatussakdiah, Halimatussakdiah; Arief, Rifqy Lamkaruna; Salsabilla, Raudhah; Tamimi, Azlya Salsabila (Universitas Syiah Kuala, 2024)
Waste cooking oil contains saturated fatty acids, which are harmful to health. Repeated use of cooking oil creates a problem that must be resolved immediately. Apart from endangering the surrounding environment, it also has a lasting effect on the families who consume the oil. Therefore, this service activity provides a solution using used cooking oil so that it can be reused as a product, namely dishwashing soap. This research is located in Blang Ara Gampong, East Seunangan District, Nagan Raya Regency. The targets for this activity are housewives who use cooking oil every day to prepare their daily food. This target aims to train mothers in the village to create household production to produce applicable value and help the family's economic income. The methods used are observation, socialization, field practice, and evaluation at the final stage of the activity. The results of this service activity help the community, especially housewives, process used cooking oil into dishwashing soap; not only does it not pollute the environment, but it also increases income. The implementation went smoothly and received a good response from the community.